Adenoid cystic carcinoma of the sublingual gland developing lung metastasis 20 years after primary treatment: A case report and literature review. Issue 49 (10th December 2021) - Ohta, Keiichi; Matsuda, Shinpei; Okada, Akitoshi; Sasaki, Masato; Imamura, Yoshiaki; Yoshimura, Hitoshi
Abstract: Rationale: Adenoid cystic carcinoma (ACC) is a rare malignant tumor that primarily occurs in the salivary glands. Distant metastases can develop despite favorable local control. Moreover, distant metastasis of ACC can occur after a long time interval without local recurrence. We report the first case of ACC of the sublingual gland that developed lung metastasis 20 years after primary treatment. Patient concerns: A 52-year-old man was referred to our department with a 1-year history of painful swelling on the right oral floor. Diagnosis: An incisional biopsy was performed, and histopathological examination revealed malignancy. Interventions: Surgical excision of the right oral floor and right supra-omohyoid neck dissection with postoperative chemoradiation therapy were performed, and ACC of the sublingual gland was diagnosed. Left pulmonary metastasis was detected 20 years after the primary treatment. Metastasectomy was performed; however, subsequently, skin and bone metastases developed. Outcomes: After receiving palliative care, the patient died of multiple organ failure. Lessons: As late distant metastasis of salivary ACC can develop, patients who undergo primary treatment need a long-term, strict follow-up plan even if locoregional control is favorable.